Pengaruh Debt To Equity Ratio, Current Ratio Dan Quick Ratio Terhadap Return On Assets - Galuh Pramesti Irawan; Gusganda Suria Manda (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The research purpose to analyze the effect of Debt to Equity Ratio, Current Ratio and Quick Ratio to Return On Assets in Food and Beverage subsector Manufacturing Companies listed on the Indonesia Stock Exchange (IDX). This research uses quantitative methods. The type of data used is secondary data in the form of financial statements during the period 2014 - 2018. This study uses multiple linear regression analysis with a hypothesis test consisting of t test and F test. The results showed that partially Debt to Equity Ratio (DER) has a significant effect to Return On Asset (ROA). Meanwhile, Current Ratio and Quick Ratio had no effect to Return On Assets (ROA). Simultaneously, DER, CR and QR have significant effect on Return On Asset (ROA). Based on the calculation of the Determination Coefficient Test it is known that the R square value is 0.294 or 29.4% which shows that 29.4% ROA can be explained by DER, CR, and QR while the remaining 70.6% is explained by other variables not analyzed in this research. Keywords: DER, CR, QR, ROA